Regioselective Synthesis of 1,4-Disubstituted 1,2,3-Triazoles: Advances in Click Chemistry and Multicomponent Reaction Engineering - Gogoi, Priyanka; Deori, Kalyanjyoti; Sarma, Diganta (Synlett, 2025)
The regioselective synthesis of 1,2,3-triazoles has emerged as a cornerstone of modern synthetic chemistry, offering immense potential in pharmaceuticals, materials science, and functional applications. This account focuses on advancing the click reaction with an emphasis on the innovations stemming from the contributions from our group. Highlights include the development of novel catalytic systems, both homogeneous and heterogeneous, and the exploration of copper-free and photocatalytic methodologies. This account bridges traditional and modern approaches, offering mechanistic insights and engineering strategies to improve regioselectivity and efficiency. This work envisions a transformative feature for azide–alkyne cycloaddition, advancing from copper-based or copper-free catalysis to light-driven innovations.1 Introduction2 Fundamentals and Mechanistic Insights of the CuAAC3 Homogeneous Catalysts for Regioselective AAC3.1 Copper-Catalyzed Homogeneous Catalytic Systems3.2 Copper-Free Homogeneous Catalytic Systems4 AAC Reactions Using Heterogeneous Catalysts4.1 Copper-Based Catalysts on Solid Supports4.2 Copper-Free Heterogeneous Catalytic Systems5 AAC Using Non-conventional Sources of Energy5.1 Microwave-Assisted Synthesis5.2 Ultrasound-Assisted Synthesis5.3 Photocatalytic AAC (PcAAC) Reactions6 Some Applications of 1,2,3-Triazoles7 Concluding Remarks and Future Scope
Keywords: click reaction; regioselectivity; azide–alkyne cycloaddition; multicomponent reaction; triazoles; light-mediated